Prevalência dos vírus da hepatite B, C e do HIV nos doadores de sangue inaptos por comportamento de risco no HEMOCE - Furlani, Stella Maria Torres (2001)
The high levei of disablement by clinicai triage seen in HEMOCE and in most of the blood centers all over the country made us develop this research whose objectives are: 1 determine the prevalence of the hepatitis virus B and C and HIV on the group unable for blood donation for risk behavior or hepatitis history after 10 years old; 2 evaluate the effectiveness of the HEMOCE triage interview to identify people with positive serology for these virus; 3 determine the main causes of disablement by the interview. 401 people underwent a questionnaire with 27 objective questions, in three sections: identification, social and economic data and epidemiologyc data. They were divided into two groups: unable (201) and able (200). Anti-HBc, Anti-HCV, Anti-HIV , VDRL and ALT were tested. Those who had Anti-HBc positive and HBS-Ag negative underwent Anti-HBs search. The HEMOCE laboratory did all the tests and the statistics methodologies used were, the Pearson íest, the Fisher exact test. The Logistic Regression models to detect factors that associate more significantly with the disablement criteria of HEMOCE. Values p<0,05 were considered meaninful. The HBsAg prevalence were 0.5% for able and 2.05% for unable while the general prevalence was 6.8% for HVB markers and 0.8% for Anti-HCV. Able were more likely to be positive for Anti-HCV than unable. Total prevalence for Anti-HIV was 0.5%. However only two persons was positive and belonged to unable (1.03%). The main reasons of disablement were sexual intercourse with unknown partner in the last six month (71.72% of the unable) and sexual intercourse with risk behavior group partner (8.08%). The fact that the donator was single and didn’t have a steady partner strong relation with partner showed strong relation with disablement (63%). The high education (74.2%) and the illiterate (64.2%) groups had higher disablement rates than the intermediary groups. The fact of using condoms irregularly (67.1%) or not (51.2%) had a negative statistic relation with disablement. Considering the lab tests as a gold standard for disablement there should be 8.1% of disabled donors.